A review of natural compounds to regulate platelet aggregation: molecular mechanism and research advance - Yi Hou; Hong Li; Luochen Zhu; Yue Li; Yue Zeng; Tian Quan; Zhangqiang Xiang; Yue Zhang; Yuan Bian; Yuxun Wei (Frontiers in Pharmacology)
Platelets are a class of blood cells exfoliated from bone marrow megakaryocytes and important participants in the blood. Aggregation is a prominent part of the platelets involved in the hemostasis process, regulated by multiple signaling pathways. Abnormal platelet aggregation could lead to thrombosis or hemorrhagic disorders, which is closely related to the abnormal expression of receptors inside and outside platelet cells and the mis-transmission of signaling factors. In recent years, natural compounds have been shown to regulate platelet aggregation on different levels, including platelet surface receptors, intracellular signaling factors, and release reaction from platelet secretory granules, due to their structiral characteristics. However, the anti-platelet aggregation mechanism of natural compounds is not comprehensive. Therefore, we have elaborated the main pathways that affect platelet aggregation in terms of the adenosine diphosphate (ADP), the levels of cAMP and cGMP, arachidonic acid (ARA) metabolism pathway, thrombin and collagen pathways in this paper. Particularly, we reviewed various natural compounds such as glycosides, coumarins, alkaloids, and acids that affect platelet aggregation mechanisms through these pathways. This review provides a reference for the application of natural compounds in the structural modification of platelet aggregation as well as in clinical studies.